2015
DOI: 10.1152/ajpcell.00399.2014
|View full text |Cite
|
Sign up to set email alerts
|

Role of domain calcium in purinergic P2X2 receptor channel desensitization

Abstract: Coddou C, Yan Z, Stojilkovic SS. Role of domain calcium in purinergic P2X2 receptor channel desensitization. Am J Physiol Cell Physiol 308: C729 -C736, 2015. First published February 11, 2015 doi:10.1152/ajpcell.00399.2014.-Activation of P2X2 receptor channels (P2X2Rs) is characterized by a rapid current growth accompanied by a decay of current during sustained ATP application, a phenomenon known as receptor desensitization. Using rat, mouse, and human receptors, we show here that two processes contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…For this purpose, we studied the patterns of currents generated by P2X2aR activation using electrophysiological techniques and tested Cdk5-mediated changes in those currents. As we have previously demonstrated, the P2X2R has a unique property, an increase in receptor desensitization rate after repetitive ATP applications that is termed use-dependent desensitization (UDD) [14; 27]. In HEK293 cells expressing the P2X2aR and measured under the whole-cell configuration, receptor desensitization increased after repetitive 10 μM ATP applications in the presence of extracellular Ca 2+ (Figure 4A).…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…For this purpose, we studied the patterns of currents generated by P2X2aR activation using electrophysiological techniques and tested Cdk5-mediated changes in those currents. As we have previously demonstrated, the P2X2R has a unique property, an increase in receptor desensitization rate after repetitive ATP applications that is termed use-dependent desensitization (UDD) [14; 27]. In HEK293 cells expressing the P2X2aR and measured under the whole-cell configuration, receptor desensitization increased after repetitive 10 μM ATP applications in the presence of extracellular Ca 2+ (Figure 4A).…”
Section: Resultsmentioning
confidence: 79%
“…We found that the activation of endogenous Cdk5, by the expression of its activator p35, significantly prevented P2X2aR desensitization after repetitive ATP applications. We have previously shown that the P2X2aR increases its desensitization rates after successive ATP applications, arising a Ca 2+ -dependent process termed UDD [14; 27]. The most plausible explanation for this phenomenon is that Cdk5-phosphorylation favors a non-desensitized phenotype and protects the receptor for the Ca 2+ -dependent UDD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26460693] ABBREVIATIONS: 17-AAG, 17-N-allylamino-17-demethoxygeldanamycin; 17-DMAG, 17-dimethylaminoethylamino-17-demethoxygeldanamycin; Bz-ATP, 29 (39)-O-(4-benzoylbenzoyl)adenosine-59-triphosphate; HEK, human embryonic kidney; HSP, heat shock protein; NMDG 1 , N-methyl-transfer across the membrane (called "current facilitation") (Yan et al, 2008(Yan et al, , 2010Khadra et al, 2013;Rokic and Stojilkovic, 2013). In contrast, the long applications of ATP needed to induce the permeability changes in P2X2Rs result in a decrease in charge transfer because the receptor desensitizes (Khakh et al, 1999;Coddou et al, 2015). The different time-dependent effects of ATP on the size of P2X2R and P2X7R currents suggest that chimeras of these channels may be useful tools to determine the locus of the HSP90 effect on P2X7R function.…”
Section: Introductionmentioning
confidence: 99%